A Water‐Stable and Red‐Emissive Radical Cation for Mutp53 Cancer Therapy. Issue 46 (17th October 2022) - Zhou, Zikai; Qian, Jieying; Liu, Kai; Zhang, Yunjiao; Gao, Meng; Tang, Ben Zhong
Abstract: Compared with conventional closed‐shell fluorophores, radical cations provide an opportunity for development of red‐to‐NIR fluorophores with small sizes and easy preparation. However, most radical cations reported in the literature suffer from poor stability in water solution and are almost non‐emissive. To tackle this challenge, we herein develop a deep‐red‐emissive and water‐stable pyrrole radical cation P⋅ + −DPA−Zn, which can be easily generated from P−DPA−Zn by air oxidation. The deep‐red‐emissive P⋅ + −DPA−Zn can be used for imaging‐guided mitochondria‐targeted delivery of Zn 2+ into cancer cells to promote mutant p53 proteins degradation and abrogate mutp53‐manifested gain of function, including reduced chemotherapy resistance, inhibited cancer cell migration, decreased tumor cell colony and sphere formation. The water‐stable and deep‐red emissive pyrrole radical cation is thus promising for cancer theranostic applications. Abstract : A water‐stable and deep‐red‐emissive radical cation P .+ −DPA−Zn was developed for mitochondria‐targeted delivery of zinc ions to promote degradation of mutp53 in cancer cells via proteasome‐dependent pathway and facilitate abrogation of various mutp53‐conferred gain of function phenotypes.